The question is attached to the post.
I'm not sure how I should start in this question.
Commutative
xy = yx
Associative
x + y = y + x
so, are they asking me to prove:
(x > y) = ( y > x)
and
(x > y) + (y > x) = (y > x) + (x > y)
This question is really confusing me.
Thanks for help in advance.
I'm not sure how I should start in this question.
Commutative
xy = yx
Associative
x + y = y + x
so, are they asking me to prove:
(x > y) = ( y > x)
and
(x > y) + (y > x) = (y > x) + (x > y)
This question is really confusing me.
Thanks for help in advance.
Attachments

44.7 KB Views: 27